External finance for low-income countries - Iqbal, Zubair; Kanbur, S. M. Ravi; IMF Institute; International Monetary Fund; World Bank (Washington, DC : International Monetary Fund, 1997)
The conference focused on the impact of external indebtedness on low-income countries, particularly the heavily indebted poor countries (HIPCs), steps being taken to deal with their debt problems, the role of official and private capital flows in the period ahead in promoting sustained growth, and policies that could be implemented to catalyze private capital flows. It afforded an important opportunity for government officials to exchange views on the complex debt issues and options to address them.
"Papers presented at the Conference on External Financing for Low-Income Countries, December 10-11, 1996, sponsored by IMF Institute, Policy Development and Review Department, International Monetary Fund [and] the World Bank."
Includes bibliographical references.
rpm 23/08/16
Loans
Keywords: Debts, External; Debt relief; Capital movements